Recent Photography Trends in Orthodontics - Hakkı Yılmaz; Fundagül Bilgiç; Özlem Akıncı Sözer (Galenos Yayinevi, 2015)
The use of photographic documentation is essential procedure in orthodontic diagnosis and treatment planning. These records are also required for legal protection. Digital technology is gaining importance for creation of photographic recording. In this article, we want to give an overview of standardization and the latest developments in the photographic field in orthodontic clinics.